2017
DOI: 10.21608/jappmu.2017.45998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Different Dietary Selenium Sources on Productive Performance, Antioxidative Properties And Immunity in Local Laying Hens Exposed to High Ambient Temperature

Abstract: The present study was carried out to compare the efficiency of different selenium (Se) sources [sodium selenite (SS), Se enriched yeast (Sel-Plex) and Nano-Se] on productive performance, lipid peroxidation, antioxidative status and immunity function of local chickens strain exposed to summer condition (high ambient temperature). One hundred and twenty birds, were randomly divided into 4 treatments: (1) control (basal diet without any supplementation of selenium), (2) SS (basal diet + 0.3 mg Se as SS / kg diet)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
0
12
2
Order By: Relevance
“…In contrast with our results, previous studies have indicated that dietary Se supplementation did not have any influence on the overall broiler performance [34,38]. Additionally, El-Deep et al [34] indicated that the addition of nano-Se (0.3 mg/kg) into laying hens' diet did not affect the FI during high environmental temperatures.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast with our results, previous studies have indicated that dietary Se supplementation did not have any influence on the overall broiler performance [34,38]. Additionally, El-Deep et al [34] indicated that the addition of nano-Se (0.3 mg/kg) into laying hens' diet did not affect the FI during high environmental temperatures.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our results, previous studies have indicated that dietary Se supplementation did not have any influence on the overall broiler performance [34,38]. Additionally, El-Deep et al [34] indicated that the addition of nano-Se (0.3 mg/kg) into laying hens' diet did not affect the FI during high environmental temperatures. This might confirm the ability of nano-Se, especially that which is synthesized by biosynthesis method at low levels (25 or 50 mg/kg), to improve the growth performance of growing rabbits in a hot environment through increasing the LBW, BWG, FI, and FCR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Shunyi et al (2016) reported that blood biochemistry of rabbits, including concentrations of alanine amino transferase (ALT) and aspartate amino transferase (AST) were not significantly affected by supplementation of nano-selenium or sodium selenite. El-Deep et al (2017) found that the birds fed diet supplemented with nano-Se recorded lower value of AST enzyme compared with control group. Also, Selim et al (2015) found that increasing supplemental nano-Se level from 0.15 to 0.30 ppm in broiler diets resulted in an increase in plasma creatinine level compared with the control group without any significant differences.…”
Section: Blood Plasma Constituentsmentioning
confidence: 85%